The Climate Change Litigation Based Human Rights Approach in Corporations: Prospects and Challenges - Yordan Gunawan; Mohammad Hazyar Arumbinang (Lembaga Contrarius Indonesia, 2023)
In recent years, the phenomenon of climate change has emerged as a critical global issue that poses a significant threat to human survival. Industries such as fossil fuels, manufacturing, and agriculture have been identified as major sources of greenhouse gas emissions. Corporate activities have played a role in triggering legal actions holding them accountable for their contribution to climate change. Therefore, this research analyses the prospects and challenges of climate change litigation against corporations in Indonesia using human rights approach. This research has adopted normative legal research with a statutory and historical approach. Descriptive analysis is applied to analyze the data. This paper reveals that the use of human rights approach can strengthen arguments against corporations over climate change. This paper concludes that despite the challenge that may arise, there is a big chance for successful climate change litigation against corporations in Indonesia by using human rights approach as the main claim.